2022
DOI: 10.1155/2022/2313416
|View full text |Cite
|
Sign up to set email alerts
|

Significance of lncRNA CDKN2B-AS1 in Interventional Therapy of Liver Cancer and the Mechanism under Its Participation in Tumour Cell Growth via miR-199a-5p

Abstract: Background and Objective. This research probed the function of lncRNA CDKN2B-AS1 (CDKN2B-AS1) in interventional therapy of liver cancer (LC) and its association with miR-199a-5p, to offer more comprehensive and reliable references for future diagnosis and therapy. Methods. Totally 34 LC patients admitted to our hospital between January 2020 and March 2021 (Obs group) and 32 healthy individuals over the same time span (Con group) were enrolled. CDKN2B-AS1 and miR-199a-5p in the two groups were PCR quantified, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…More in vivo and ex vivo experiments are needed for validation in the future. 65 STAT3 can induce ARlncRNA HAGLROS overexpression and thus activate mTOR signaling to inhibit autophagy and promote malignant progression in GC cells. HAGLROS regulates mTOR signaling in two ways.…”
Section: Arlncrnas Promote Tumor Migration and Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…More in vivo and ex vivo experiments are needed for validation in the future. 65 STAT3 can induce ARlncRNA HAGLROS overexpression and thus activate mTOR signaling to inhibit autophagy and promote malignant progression in GC cells. HAGLROS regulates mTOR signaling in two ways.…”
Section: Arlncrnas Promote Tumor Migration and Invasionmentioning
confidence: 99%
“… 53 In another in vitro study, hepatocellular carcinoma cells exhibited weaker viability, invasive and migratory activities, and stronger apoptotic activity after silencing ARlncRNA CDKN2B-AS1 and up-regulating miR-199a-5p. 65 In in vivo studies, inhibition of tumor cell growth was observed after the knockdown of ARlncRNA MALAT-1, HULC, DANCR, and LCPAT1. 6 , 50 , 80 , 81 By the same token, up-regulation of oncogenes is also an effective anti-tumor strategy.…”
Section: The Clinical Significance Of Arlncrnasmentioning
confidence: 99%
“…Moreover, miR-199a-5p was considered as a vital mediator in tumor progression. For instance, miR-199a-5p could promote the tumorigenesis of oral squamous cell carcinoma through regulating SMARCA4 (18); Xu et al (19) suggested lnc CDKN2B-AS1 was implicated in the development and progression of liver cancer by suppressing cell autophagy through targeting miR-199a-5p. Meanwhile, miR-199a-5p was involved in lncRNA TINCR-mediated progression of BC (20).…”
Section: Introductionmentioning
confidence: 99%